Variasi Temperatur Pencampuran terhadap Parameter Marshall pada Campuran Lapis Aspal AC-BC - M Aldi Muhtaibillah A; Jasman Jasman; Hamsyah Hamsyah; Adnan Adnan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Mixing temperature has an important role in the performance of the asphalt mixture that has been made. If the mixing temperature is too low and causes the viscosity value to be high, it will make it difficult to carry out asphalt mixing and was studied in the laboratory for two months which aims to determine the effect of mixing temperature variations on the value of marshall parameters and determine the effect of temperature variations on the performance of AC-WC asphalt pavement mixing. Characteristics of Temperature Variations in AC-BC asphalt mixtures for temperature variations of 140, 150 and 160, from the results of testing vim at a temperature of 160 with a value of 6.63 does not meet specifications, at a VFB value at a temperature of 160 does not meet specifications with a VFB value of 64.25, for the value of stablity, VMA, flow, MQ all meet specifications. so it can be concluded that the greater the temperature can make the asphalt mixture ineffective or the quality of the AC-BC asphalt decreases. The effect of temperature variation on AC-BC asphalt mixture is not optimal because the greater the temperature parameter can reduce the quality of AC-BC. The results of the proof of the marshal test of several temperature variations that do not meet the specifications make some marsall tests not pass specifications and density results that are not solid.